Formal Specifications and Analysis of an Agent-Based Model for Cognitive Aspects of Fear of Crime - Ab. Aziz, Azizi; Mohd Shabli, Ahmad Hanis; Ghanimi, Hayder M. A. (Springer, Cham, 2017)
This paper presents a cognitive agent model of fear of crime. The proposed model takes personality, environment, and perception of several events as input and calculates internal factors related to cognitive fear of crime, such as the belief about safety, community trust and likelihood of crime activities, and how they affect individual fear of crime. Simulation results suggest that community level of fear of crime and trust may emerge as the outcome of individuals’ reaction towards perception of crime activities related to their exogenous properties. In addition, a formal approach is put forward to evaluate the behaviours of the proposed model by means of formal techniques namely; mathematical analysis, parameter evaluation, and automated logical verification. The first and second approaches analyse the equilibria conditions and follow by automatically checking a number of expected properties as depicted in the literature. One of the major contributions of this model is the possibility that an analytical engine could be further developed to support community wellbeing.